Junie B. Jones has a monster under her bed - Park, Barbara; Brunkus, Denise (New York : Random House, 1998)
After hearing from a classmate at kindergarten that people have monsters under their beds, Junie B. Jones is afraid to go to sleep that night.
"A stepping stone book."
Keywords: Monsters -- Fiction; Bedtime -- Fiction; Fear -- Fiction; Kindergarten -- Fiction; Schools -- Fiction